2015
DOI: 10.3389/fpsyt.2015.00132
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and Smoking-Associated DNA Methylation Changes at HIV Co-Receptor GPR15

Abstract: Smoking is associated with poorer health outcomes for both African and European Americans. In order to better understand whether ethnic-specific genetic variation may underlie some of these differences, we compared the smoking-associated genome-wide methylation signatures of African Americans with those of European Americans, and followed up this analysis with a focused examination of the most ethnically divergent locus, cg19859270, at the GPR15 gene. We examined the association of methylation at this locus to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 44 publications
0
35
1
Order By: Relevance
“…In their next study, the same authors found that methylation of GPR15 locus that was dependent on the ethnicity and hypomethylation were found only in African Americans. 41 However, several following studies have found the highly significant (with genome-wide significance) hypomethylation and increased expression of GPR15 in smokers. [42][43][44] Another study analyzed the RNA expression from the whole blood together with methylation profile and found highly significant upregulation of GPR15 expression in the blood that correlated with the hypomethylation of the GPR15 locus.…”
Section: Gpr15 and Smokingmentioning
confidence: 99%
“…In their next study, the same authors found that methylation of GPR15 locus that was dependent on the ethnicity and hypomethylation were found only in African Americans. 41 However, several following studies have found the highly significant (with genome-wide significance) hypomethylation and increased expression of GPR15 in smokers. [42][43][44] Another study analyzed the RNA expression from the whole blood together with methylation profile and found highly significant upregulation of GPR15 expression in the blood that correlated with the hypomethylation of the GPR15 locus.…”
Section: Gpr15 and Smokingmentioning
confidence: 99%
“…Analyses for cg03636183 were stratified by ancestry (African or European), because methylation of cg03636183 has been shown to vary by population (Dogan et al . ; Zhang et al . ).…”
Section: Methodsmentioning
confidence: 99%
“…), among both sexes (Dogan et al . ), across a wide range of ages (Beach et al . ) and different tissues (Stueve et al .…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of these allele variants among Native American groups is unknown (44). This rationale follows for other cases as well considering a differential SNP mutation in rs2230344, a loci within the promoter region of GPR15, was observed within the AA cohort in Dogan et al's analysis (70).…”
Section: Differences In Response To Environmental Toxinsmentioning
confidence: 95%
“…Dogan et al, on the other hand, discovered that GPR15, a chemokine receptor involved in human immunodeficiency virus (HIV) propagation, was significantly differentially methylated in AA smokers when compared with Caucasian smokers. The group also mentioned that this could point towards a causal pathway for the increased prevalence of HIV within the AA community as the loss of function in the GPR15 gene may leave patients in this demographic subset at increased risk for HIV susceptibility (70).…”
Section: Differences In Response To Environmental Toxinsmentioning
confidence: 99%